Hybrid methods of finishing wooden elements after milling: sanding, impregnation, varnishing in an automatic cycle - Dashkovskyi, Leonid (Global Prosperity, 2025)
Abstract. The production of modern wooden elements requires parts with much greater geometric accuracy and surface geometry (SG) precision than a few years ago. These requirements are met by so-called hybrid technologies, which must also be inexpensive to implement. The integration of processing procedures (usually in a single operation) is aimed at achieving a synergistic effect. The combination of different processes from different technologies provides synergy, i.e., advantages greater than the optimization of each individual process performed separately. This article presents experimental results and data from numerical experiments on the finishing of wooden elements. The hybrid technology used in the study was a combination of milling and finishing with lacquering. These processes were integrated on a multi-axis CNC machining center. The results show that milling across the grain produces more burrs on the wood surface than milling parallel to and against the grain. Plastic deformations of real surfaces were determined using simulations. The article also discusses the structure of the model and how it can be used for computer simulation using the finite element method (FEM). It has been proven that laser processing is more efficient than traditional manual processing. The aim of the study was to determine how to use the potentially developed hybrid processing model to predict surface characteristics expressed by amplitude, volume, and functional parameters of surface geometry.